In Vitro Evaluation of Apical Debris Extrusion Using Different Rotary File Systems in Extracted Mandibular Premolars (Nigerian Dental Journal, 2026)
ObjectivesThis in vitro study aimed to compare the amount of apically extruded debris generated during root canal preparation using three contemporary nickel–titanium file systems with different design features and kinematics: TruNatomy, HyFlex EDM, and WaveOne Gold.MethodsEighty-seven extracted single-rooted mandibular premolars were randomly assigned to three groups (n = 29). Canal preparation was performed according to the manufacturers' instructions for each system. Irrigation was standardized using 10 mL of distilled water per canal. Apically extruded debris was collected in pre-weighed Eppendorf tubes, dried at 70 °C for 5 days, and weighed using an analytical balance. Statistical analysis was performed using one-way ANOVA with appropriate post hoc tests or the Kruskal–Wallis test, depending on data distribution. The significance level was set at P < 0.05. ResultsA statistically significant difference in the amount of apically extruded debris was observed among the groups (P < 0.001). TruNatomy produced significantly less debris (mean ± SD: 0.018 ± 0.006 g) compared with HyFlex EDM (mean ± SD: 0.031 ± 0.006 g) and WaveOne Gold (mean ± SD: 0.027 ± 0.008 g). No significant difference was detected between the HyFlex EDM and WaveOne Gold systems (P > 0.05). ConclusionWithin the limitations of this in vitro model, apical debris extrusion differed among rotary systems with distinct design characteristics and kinematics. TruNatomy was associated with lower debris extrusion than HyFlex EDM and WaveOne Gold under standardized laboratory conditions. These findings should be interpreted as comparative experimental data, as periapical tissue resistance and clinical irrigation dynamics were not simulated.Keywords: Apical debris extrusion; Root canal preparation; Nickel–titanium instruments; TruNatomy; WaveOne Gold; HyFlex EDM
Keywords: Apical debris extrusion; Root canal preparation; Nickel–titanium instruments; TruNatomy; WaveOne Gold; HyFlex EDM